2016
DOI: 10.1007/s10549-016-3835-7
|View full text |Cite
|
Sign up to set email alerts
|

Biological subtyping of early breast cancer: a study comparing RT-qPCR with immunohistochemistry

Abstract: The biological subtype of breast cancer influences the selection of systemic therapy. Distinction between luminal A and B cancers depends on consistent assessment of Ki-67, but substantial intra-observer and inter-observer variability exists when immunohistochemistry (IHC) is used. We compared RT-qPCR with IHC in the assessment of Ki-67 and other standard factors used in breast cancer subtyping. RNA was extracted from archival breast tumour tissue of 769 women randomly assigned to the FinHer trial. Cancer ESR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 18 publications
(30 reference statements)
5
42
1
4
Order By: Relevance
“…To exclude any effect of the sample selection on ICC results, the ICCs were again computed using the intersample variance observed in the 769 breast cancer cases of the FinHer trial [27] along with the intersite and residual variance extracted from the present reproducibility study. The marker-specific ICCs in this analysis were nearly identical (Table 4, lower panel ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To exclude any effect of the sample selection on ICC results, the ICCs were again computed using the intersample variance observed in the 769 breast cancer cases of the FinHer trial [27] along with the intersite and residual variance extracted from the present reproducibility study. The marker-specific ICCs in this analysis were nearly identical (Table 4, lower panel ).…”
Section: Resultsmentioning
confidence: 99%
“…The challenges in the standardization of Ki67 assessment include the variability in the selection of the tumor areas to be assessed, the technique used for nuclei counting, and the dilemma of the numerical cutoff for positivity, especially for large tissue sections [8, 9, 15, 16]. The highly promising reproducibility of the MammaTyper® was confirmed by a simulated analysis using MammaTyper® data obtained from 769 samples from the FinHer trial cohort [27], verifying that the study samples were representative of the whole spectrum of routine clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found a high rate of agreement between mRNA‐based and IHC‐based intrinsic subtyping in ER‐positive/HER2‐negative early BCs, with comparable rates of agreement when either the Ki67‐LI (84%, κ = 0.679) or the MAI (89%, κ = 0.779) was used. Like others, we found high rates of agreement between dichotomised IHC assessment and mRNA‐based measurement of ER, HER2 and PR expression (100%, 100%, and 95%, respectively) 28 . HER2‐positive BCs were not included in our study, because chemotherapy recommendations are straightforward in these patients, whereas the decisions for or against cytotoxic treatment in patients with ER‐positive/HER2‐negative BC mainly depend on proliferative activity 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The crucial point in subtyping of luminal cancers remained, however, the assessment of proliferative activity, for which we found a moderate to strong linear correlation between MKI67 and the Ki67‐LI ( R = 0.67 for Ki67‐G, and R = 0.74 for Ki67‐H) and MAI ( R = 0.67). Our achieved agreement between mRNA MKI67 and IHC + MAI or Ki67‐G dichotomisation of proliferation was considerably higher than previously described (82%, κ = 0.62 for IHC + Ki67‐G with 20% as a cut‐off, and 88%, κ = 0.747 for IHC + MAI versus 75%, κ = 0.45 for Ki67 in FinHer) and may be due to decentralised, non‐standardised Ki67 assessment in the FinHer study 28. In fact, the rates of agreement between MammaTyper and IHC in our work were also influenced by the proliferation assessment methods and cut‐offs used.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the tumor with Ki-67 mRNA expression may be valuable for election patients for adjuvant therapy containing docetaxel [25].…”
Section: Discussionmentioning
confidence: 98%